A bridging cell multiscale modeling of carbon nanotube-reinforced aluminum nanocomposites. (15th October 2018) - Iacobellis, Vincent; Radhi, Ali; Behdinan, Kamran
Abstract: In this paper, the Young's modulus and failure mechanics of nanotube-reinforced aluminum nanocomposites has been investigated using the Bridging Cell Method (BCM). The advantage of the BCM for multiscale modeling of CNT-Al nanocomposites is in its quasi-static formulations in concurrent multiscale environment with specialized local quasi-harmonic approximations for thermal contributions. The model has been initially verified by coupling the atomistic-continuum domains in a representative volume element of the nanocomposite. The multiscale method sets the nanotubes as part of the atomistic domain, while the rest of the domain is kept in the continuum domain and modeled using the finite element method. The types of nanotube reinforcements considered in this study are single-walled nanotubes (SWNTs), multi-walled nanotubes (MWNTs) and a bundle of SWNTs. It was found that the overall strength of the nanocomposite was similar between the different reinforcements, but the toughening mechanisms differed significantly between the three. The model has been tested for two different crystalline planes in the aluminum crystal to observe the degree of toughening on different atomic planes where it was found that the essential plane and the cleavage plane had similar ultimate tensile strength, however the role of toughening was less prevalent in the cleavage plane case.